2000
DOI: 10.1002/1097-4628(20000808)77:6<1393::aid-app27>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Key properties to understand the performance of polycarbonate reprocessed by injection molding

Abstract: The reprocessing of injection‐molded polycarbonate was studied in an attempt to understand the physical background for the variation of its performance upon sequential molding cycles. The effect of reprocessing on different properties of the moldings and the regrind is presented and discussed. A quantitative analysis of the Fourier transform IR spectra indicates that phenol and carbon dioxide are released during the initial cycles, probably due to molecular scission near the chain ends. Most of the results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Similar results have been obtained by other authors. For example, Liu et al (2000) showed that during the reprocessing of injection-molded polycarbonate, the flow index increases slightly but continuously, through the first four cycles, stabilizing thereafter. Chrysostomou and Hashemi (1996) have shown that flow index values increase slightly from the virgin material to the five-time recycled material.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Similar results have been obtained by other authors. For example, Liu et al (2000) showed that during the reprocessing of injection-molded polycarbonate, the flow index increases slightly but continuously, through the first four cycles, stabilizing thereafter. Chrysostomou and Hashemi (1996) have shown that flow index values increase slightly from the virgin material to the five-time recycled material.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Polyamides have good dimensional stability, high rigidity (especially when PA is reinforced with fi breglass), good resistance to compression, wear, shocks and vibra# ons; they are hard materials, and maintain their hardness and tenacity at high temperatures, with no visible transforma# ons up to 80-90°C [3][4][5][6][7][8][9]. PAs are semitransparent in moulded parts with thin wall and opaque in moulded parts with thick wall.…”
Section: Introductionmentioning
confidence: 99%
“…These properties offer high use value in fields which require materials with advanced characteristics: dimensional stability, resistance to UV radiation, solvents, aggressive chemical agents [1][2][3][4][5][6][7], impact resistance, and possibility of use in a wide range of temperatures etc. Properties result from a set of summed specific characteristics of individual materials, which arise from physical, mechanical and chemical interactions that occur during manufacturing processes that result in a polymer nanostructure.…”
Section: Introductionmentioning
confidence: 99%